Estimativa do balanço de energia na bacia do Baixo Jaguaribe utilizando técnicas de sensoriamento remoto. - Peixoto, Eduardo de Almeida Guimarães (2009)
Using techniques of remote detection, this work aimed to obtain the energy balance in the Basin of Low Jaguaribe, Perimeter irrigated Tabuleiro de Russas and dam Santo Antônio de Russas. Two images of sensor TM of the satellite Landsat 5 obtained together DGI (Department of Generation of Images) of INPE, composed by six bands, (1,2,3,4,5,7) of the spectrum of the visible and a thermal band, (6) dated of 13/08/2007 and 28/09/2008, were used for this. After, I linked the variations of the obtained results, with the indexes of rain observed in four pluviometers, belonging to FUNCEME, entered in the study area. There was not rain registration during the five previous days the image of 2007, already in 2008, three pluviometers registered 14 mm, 15 mm and 3,2 mm.The processing of the images, the Software ERDAS 8.7 was used, being used for the estimate of the energy balance, the method proposed by the algorithm SEBAL (Surface Energy Balancy Algorithm Land). This algorithm calculated: reflectance, vegetation indexes, temperature of the surface, radiation balance, flow of sensitive heat, flow of latent heat among others. For the obtaining of some of those parameters was used surface data obtained in the automatic station of the municipal district of Russas. The medium reflectance, in 2008, was of 0,249. and in 2007, it was of 0,236, being verified a small increase in 2008. The Index of Vegetation of the normalized difference presented average of 0,376 in 2008, and 0,162 in 2007, being verified a strong influence of the rains in that parameter. The radiation balance in 2007, 570 W/m², was higher than 2008, 522 W/m². I concluded that this increase is related with smaller reflectance index and larger incidence of the radiation of short waves in 2007. The flow of sensitive heat in 2007 was of 303 W/m² and, in 2008, it was of 185 W/m², observed that the rains, in 2008, will reduce the flow of sensitive heat. The flow of latent heat presented opposite values to the flow of sensitive heat as expected. In 2007 the obtained average was 162 W/m², and in 2008, it increased due ace rains, for 272 W/m².